Preclinical profile of a dopamine D1 potentiator suggests therapeutic utility in neurological and psychiatric disorders - Bruns, Robert F.; Mitchell, Stephen N.; Wafford, Keith A.; Harper, Alex J.; Shanks, Elaine A.; Carter, Guy; O'Neill, Michael J.; Murray, Tracey K.; Eastwood, Brian J.; Schaus, John M.; Beck, James P.; Hao, Junliang; et al. (Neuropharmacology, 2018)
DETQ, an allosteric potentiator of the dopamine D1 receptor, was tested in therapeutic models that were known to respond to D1 agonists. Because of a species difference in affinity for DETQ, all rodent experiments used transgenic mice expressing the human D1 receptor (hD1 mice). When given alone, DETQ reversed the locomotor depression caused by a low dose of reserpine. DETQ also acted synergistically with L-DOPA to reverse the strong hypokinesia seen with a higher dose of reserpine. These results indicate potential as both monotherapy and adjunct treatment in Parkinson's disease. DETQ markedly increased release of both acetylcholine and histamine in the prefrontal cortex, and increased levels of histamine metabolites in the striatum. In the hippocampus, the combination of DETQ and the cholinesterase inhibitor rivastigmine increased ACh to a greater degree than either agent alone. DETQ also increased phosphorylation of the AMPA receptor (GluR1) and the transcription factor CREB in the striatum, consistent with enhanced synaptic plasticity. In the Y-maze, DETQ increased arm entries but (unlike a D1 agonist) did not reduce spontaneous alternation between arms at high doses. DETQ enhanced wakefulness in EEG studies in hD1 mice and decreased immobility in the forced-swim test, a model for antidepressant-like activity. In rhesus monkeys, DETQ increased spontaneous eye-blink rate, a measure that is known to be depressed in Parkinson's disease. Together, these results provide support for potential utility of D1 potentiators in the treatment of several neuropsychiatric disorders, including Parkinson's disease, Alzheimer's disease, cognitive impairment in schizophrenia, and major depressive disorder. •The dopamine D1 potentiator DETQ was tested in humanized D1 mice and rhesus monkeys.•Actions of DETQ were dependent on endogenous dopaminergic tone.•DETQ displayed a behavioral profile consistent with central D1 receptor activation.•Neurochemical actions of DETQ support potential pro-cognitive effects.•D1 potentiators show promise for Parkinson's disease and other CNS disorders.